Comparative Analysis of Concrete Curing Using the Water Curing Method and the Geotextile Non-Woven Membrane Curing Method and Their Effects on Concrete Compressive Strength - Lely Hendarti; Daffa Ashshiddiq; Silvia Yulita Ratih Setyo Rahayu (Asosiasi Dosen Muda Indonesia, 2026)
This study compares the effectiveness of conventional water curing and non-woven geotextile membrane curing on concrete compressive strength, an important issue because curing quality strongly influences early hydration and strength development while field constraints often limit continuous water-based curing. A quantitative experimental design was conducted in a controlled laboratory setting using 150 mm concrete cube specimens produced with a standardized mix design; specimens were assigned to either full water immersion or pre-moistened non-woven geotextile membrane curing. Compressive strength data were collected at 7, 14, and 28 days and analyzed descriptively by comparing average strengths and strength development trends between both curing methods. The results show that strength increased with age under both regimes, while membrane curing consistently achieved slightly higher average compressive strength than water curing, with the largest difference at 7 days (28.56 MPa vs. 26.95 MPa) and smaller gaps at 14 days (33.04 MPa vs. 32.58 MPa) and 28 days (38.61 MPa vs. 37.99 MPa). These findings suggest that non-woven geotextile membrane curing can be a practical alternative to water curing, particularly where continuous immersion or water supply is difficult to maintain, because it may provide better early-age moisture retention without compromising later-age strength. The originality of this study lies in presenting direct experimental evidence comparing immersion-based curing and an accessible non-woven geotextile membrane approach across multiple curing ages under consistent specimen production conditions.